The barrier functions of crude cervical mucus plugs against HIV-1 infection in the context of cell-free and cell-to-cell transmission. (1st November 2021) - Mhlekude, Baxolele; Lenman, Annasara; Sidoyi, Phikolomzi; Joseph, Jim; Kruppa, Jochen; Businge, Charles Bitamazire; Mdaka, Mana Lungisa; Konietschke, Frank; Pich, Andreas; Gerold, Gisa; Goffinet, Christine; Mall, Anwar Suleman
Abstract : Objective: The cervical mucus plugs are enriched with proteins of known immunological functions. We aimed to characterize the anti-HIV-1 activity of the cervical mucus plugs against a panel of different HIV-1 strains in the contexts of cell-free and cell-associated virus. Design: A cohort of consenting HIV-1-negative and HIV-1-positive pregnant women in labour was recruited from Mthatha General Hospital in the Eastern Cape province of South Africa, from whom the cervical mucus plugs were collected in 6 M guanidinium chloride with protease inhibitors and transported to our laboratories at −80 °C. Methods: Samples were centrifuged to remove insoluble material and dialysed before freeze--drying and subjecting them to the cell viability assays. The antiviral activities of the samples were studied using luminometric reporter assays and flow cytometry. Time-of-addition and BlaM-Vpr virus-cell fusion assays were used to pin-point the antiviral mechanisms of the cervical mucus plugs, before proteomic profiling using liquid chromatography-tandem mass spectrometry. Results: The proteinaceous fraction of the cervical mucus plugs exhibited anti-HIV-1 activity with inter-individual variations and some degree of specificity among different HIV-1 strains. Cell-associated HIV-1 was less susceptible to inhibition by the potent samples whenever compared with the cell-free HIV-1. The samples with high antiviral potency exhibited a distinct proteomic profile when compared with the less potent samples. Conclusion: The crude cervical mucus plugs exhibit anti-HIV-1 activity, which is defined by a specific proteomic profile. Abstract : Supplemental Digital Content is available in the text